Factors that attract Filipinos to join multilevel marketing companies - Ramiscal, Vannessa Sarino (Animo Repository, 2006)
The number of people joining multilevel marketing companies has made an impact on how products and services are distributed in our country because these people are the ones selling the products and recruiting prospect members to join MLM companies. Studying the factors that affect the perception of Filipinos to join or not join MLM companies can lead to insights on how MLM companies can improve what they offer to the market. To determine the factors, this study utilized Scotts Rational Choice Theory to theorize that actions and decisions are basically rational in character and people calculates the different costs and benefits of any action before making a decision. The relationship of costs and benefits were evaluated using Kotler's Determinants of customer added value. This study provides a unique contribution to MLM industry because it specifically defines what factors affect the decision to join or not join MLM companies among the 3 membership status in the MLM industry (former members, current members, and non-members).